Assessing the Potential of Thailand’s National Forest Reserves for Tourism Development and Sustainable Recreational Use - Pongpattananurak, Nantachai; Phumsathan, Sangsan (Forest and Society, 2025)
This research aimed to evaluate the potential of Thailand's national forest reserves for promoting sustainable recreational activities. Research tools included a comprehensive tourism potential assessment form for evaluating tourism development. Additionally, semi-structured interviews and focus group meetings with key informants were conducted to gain insights into local perspectives, challenges, and opportunities related to tourism. Site surveys were conducted during January - August 2021. The study initially conducted an assessment of 122 destinations located within 85 national forest reserves across the country to determine their tourism development potential. Subsequently, 16 national forest reserves exhibiting high potential were selected for on-site surveys. These revealed a diverse range of recreational resources within the national forest reserves, including waterfalls, rapids, rivers, viewpoints, ecotourism sites, nature trails, hot springs, caves, geographic landscapes, and archaeological sites. The assessment of tourism development potential identified six areas with high potential, eight areas with medium potential, and two areas with low potential within the national forest reserves. To effectively promote recreation and sustainable tourism in Thailand's national forest reserves, the Royal Forest Department, responsible for overseeing these areas, should prioritize the following key considerations: 1) development of interpretive programs that align with the unique features and highlights of each area to enhance visitors' learning experiences, 2) active involvement of local communities in tourism development initiatives, and 3) provision of basic service facilities to support visitor activities. This is a normative assessment, and future studies should focus on the ways that tourism is reshaping these landscapes and livelihoods.